2019
DOI: 10.1111/1744-7917.12656
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and comparative analysis of transcripts encoding chemosensory proteins from two plant bugs, Lygus lineolaris and Lygus hesperus

Abstract: Chemosensory proteins (CSPs) are soluble carrier proteins typically characterized by a six-helix bundle structure joined by two disulfide bridges and a conserved Cys spacing pattern (C1-X 6-8 -C2-X 16-21 -C3-X 2 -C4). CSPs are functionally diverse with reported roles in chemosensation, immunity, development, and resistance. To expand our molecular understanding of CSP function in plant bugs, we used recently developed transcriptomic resources for Lygus lineolaris and Lygus hesperus to identify 17 and 14 CSP-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 114 publications
(198 reference statements)
0
3
0
Order By: Relevance
“…Hull et al [ 215 ] used homology-based cloning methods and transcriptome data mining to identify guanine-nucleotide binding proteins (G proteins) to elucidate the molecular mechanisms driving signal transduction in L. hesperus . Hull et al [ 216 ] recently defined the Lygus chemosensory proteins (CSPs) that play roles in chemosensation, development, immunity, and resistance. This study identified 17 CSP-like sequences in L. lineolaris and 14 sequences in L. hesperus , and these Lygus CSPs are orthologues and share sequence identity to previously annotated CSPs from other hemipterans.…”
Section: Integrated Management Strategiesmentioning
confidence: 99%
“…Hull et al [ 215 ] used homology-based cloning methods and transcriptome data mining to identify guanine-nucleotide binding proteins (G proteins) to elucidate the molecular mechanisms driving signal transduction in L. hesperus . Hull et al [ 216 ] recently defined the Lygus chemosensory proteins (CSPs) that play roles in chemosensation, development, immunity, and resistance. This study identified 17 CSP-like sequences in L. lineolaris and 14 sequences in L. hesperus , and these Lygus CSPs are orthologues and share sequence identity to previously annotated CSPs from other hemipterans.…”
Section: Integrated Management Strategiesmentioning
confidence: 99%
“…Despite TPB being a pest of several economically important crops grown in North America, apart from a few population genetic and transcriptome and gene expression studies, there is a general paucity of research on the genetics of TPB [26][27][28][29][30][31]. Therefore, the development of a comprehensive set of genetic resources including a high-quality genome, full transcriptome with an o cial gene set that identi es all isoforms, and genetic markers suitable for population genomic and quantitative genetic studies is in need for this species.…”
Section: Introductionmentioning
confidence: 99%
“…Despite TPB being a pest of several economically important crops grown in North America, apart from a few population genetic and transcriptome and gene expression studies, there is a general paucity of research on the genetics of TPB [ 26 – 31 ]. Therefore, the development of a comprehensive set of genetic resources including a high-quality genome, full transcriptome with an official gene set that identifies all isoforms, and genetic markers suitable for population genomic and quantitative genetic studies is needed for this species.…”
Section: Introductionmentioning
confidence: 99%